Experimental analysis of entrance and exit damage mechanism affected by the structural dynamic deformation characteristics during drilling of thin-walled CFRP. (November 2022) - Cao, Sipeng; Zhang, Kaifu; Hou, Guoyi; Luo, Bin; Cheng, Hui; Li, Yuan; Li, Ximing; Liu, Chinan
Abstract: Due to lack of effective backup when drilling aircraft thin-walled CFRP structure, serious dynamic structural deformation including vertical and in-plane deformation usually occur, which extremely changes the cutting behavior and materials removed mechanism, causing severe entrance and exit damages. Therefore, this paper proposed a dynamic deformation measurement experiment in vertical and horizontal direction at various processing parameters to analyze their effects on cutting mechanism and damages distribution. Results show the vertical and in-plane deformation occurrence are highly dependent on the actual positions of tool-CFRP system. Namely elastic deformation, local deformation and drawback reflection appear many a time in different stages, causing obvious sudden change of thrust force and different initiation and propagation characteristics of damages. With the feed rate increasing and workpiece thickness decreasing, the maximum displacements of every stages all increase and some thinner workpiece displacement exceed several times the plate thickness. The larger in-plane deformation will nonuniformly distribute along borehole exit due to the different cutting mechanism and strength of different fiber cutting angles. The larger elastic deformation and drawback action in vertical direction will change the out-ply material remove mechanism into mainly puncture rather than only cutting. Under the joint action of deformation in two directions, the loose surface damages composed of delamination and uncut fiber will gather heavily at exit. Highlights: The vertical and in-plane deformation were characterized in divided stages by DIC. The influence of drilling parameters on deformation and drawback was investigated. The cutting behavior at various FCA under large drawback action was revealed. The damage formation and propagation mechanism of drilling process was analyzed. The in-plane damages in entrance and exit regions after deformation were evaluated.